Balancing carbon/nitrogen ratio to improve nutrients removal and algal biomass production in piggery and brewery wastewaters. (February 2018) - Zheng, Hongli; Liu, Mingzhi; Lu, Qian; Wu, Xiaodan; Ma, Yiwei; Cheng, Yanling; Addy, Min; Liu, Yuhuan; Ruan, Roger
Highlights: Piggery wastewater exhibited low carbon/nitrogen mass ratio. Brewery wastewater had high carbon/nitrogen mass ratio. Mixing the wastewaters balanced the carbon/nitrogen mass ratio. The optimal carbon/nitrogen mass ratio of mixed wastewater was 7.9. Strategies for enhancing nutrients removal and biomass production were established. Abstract: To improve nutrients removal from wastewaters and enhance algal biomass production, piggery wastewater was mixed with brewery wastewaters. The results showed that it was a promising way to cultivate microalga in piggery and brewery wastewaters by balancing the carbon/nitrogen ratio. The optimal treatment condition for the mixed piggery-brewery wastewater using microalga was piggery wastewater mixed with brewery packaging wastewater by 1:5 at pH 7.0, resulting in carbon/nitrogen ratio of 7.9, with the biomass concentration of 2.85 g L −1, and the removal of 100% ammonia, 96% of total nitrogen, 90% of total phosphorus, and 93% of chemical oxygen demand. The application of the established strategies can enhance nutrient removal efficiency of the wastewaters while reducing microalgal biomass production costs.